An Initiative to Standardize the Identification of and Acute Response to Postoperative Lower-Extremity Neurological Deficits: Effects on Provider Knowledge, Confidence, and Communication Skills. (7th December 2016) - Derman, Peter B.; Iyer, Sravisht; Garner, Matthew; Orr, Steven; Felix, Karla J.; Goldberg, Allison; Ologhobo, Titilayo; Wu, Minlun; Robbins, Laura; Cornell, Charles
Abstract : Background: Although relatively uncommon, neurological deficits following hip and knee arthroplasty can have permanent and debilitating consequences. This study was conducted to quantify the effectiveness of an educational curriculum aimed at standardizing the identification of and acute response to postoperative neurological deficits in the inpatient setting, specifically with respect to improvements in clinician knowledge, confidence levels, and communication skills. Methods: A multidisciplinary committee at a single, high-volume academic institution created an algorithm delineating the appropriate clinical actions and escalation procedures in the setting of a postoperative neurological deficit for each clinical practitioner involved in care for patients who undergo arthroplasty. An educational curriculum composed of online learning modules and an in-person "boot camp" featuring simulations with standardized patients was developed, along with assessments of clinician knowledge, confidence levels, and communication skills. Nurses, physical therapists, physician assistants, residents, fellows, and attending surgeons were encouraged to participate. The intervention spanned a 5-month period in 2015 with a mean time of 18.4 weeks between baseline assessments and the time of the latest follow-up. Results: Online modules were completed by 322 individuals, boot camp was completed by 70 individuals, and latest assessments were completed by 38 individuals. The percentage correct on the knowledge assessment increased from 74.5% before the learning modules to 89.5% immediately after (p < 0.001) but degraded over time such that there was no significant difference between baseline and the latest follow-up scores (p = 0.11). Over the course of the boot camp, physician assistants and residents successfully performed approximately 91% of the indicated actions on the scoring rubric; physical therapists and nurses successfully performed 78%. Scores on the communication skills assessment showed a significant mean increase (p = 0.02) over the course of the intervention from 30.32 to 32.50, and the mean self-assessed confidence survey scores increased by 16.7%, from 7.2 to 8.4 (p < 0.001). Conclusions: A multimodality educational curriculum aimed at quality improvement can produce significant knowledge improvements, but these gains may not be maintained over time without further instruction. Gains in confidence and communication skills appear to be more long-lasting.